O dirigente público como categoria analítica: um exercício de definição - Bonis, Daniel Funcia de (2008)
This work is built on the premise of the insufficiency of the typologies based on the distinction between politicians and bureaucrats to the proper understanding of the workings of the contemporaneous democratic State, since these approaches downplay the importance of the public executive as a distinct and relevant player in these processes. Therefore, we develop an exercise of defining the public executive as a distinct analytical category from politicians and bureaucrats alike, building, with the support of the variables discussed on the relevant literature, a theoretical model of the public executive as a political actor whose ethos is economic rationality, from whom managerial competences, capacity of judgment and responsiveness to the elected politician are expected. Public executives work on short tenures, are selected by formal or informal processes in which his or hers competences and potential loyalty are assessed, and come either from the pool of public servants available on the specific governmental agency for which they are chosen or from the private or nonprofit sector, academic institutions, or other governmental spheres. Empirical observations made with public executives working for the São Paulo Municipality between September 2007 and January 2008 contributed to reinforce and qualify this definition. We hope that the conclusions of this study can contribute to the consideration of the public executive as an important element on research agendas regarding the contemporaneous democratic institutions, besides offering elements to proposals of public administration reform in Brazil that point towards the institutionalization of the public executive function in our country.